THE CORELATION BETWEEN MOTHER'S WEIGHT INCREASE WITH PRE-ECLAMPSION IN PREGNANCY AT SITI KHOLIZAH CLINIC - Sebayang Wellina; Sinaga Elvalini Warnelis; Simamora Debora Lestari (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Pre-eclampsia/eclampsia is one of the main causes of maternal death in Indonesia. The cause of pre-eclampsia in pregnant women is not known with certainty, although there have been several theories that try to explain the cause of pre-eclampsia is placental ischemia. The purpose of this study was to see the relationship between maternal weight gain and the incidence of preeclampsia in pregnancy. This type of research is an observational retrospective analytic study. Analytical observational research. The research location was at the Siti Kholizah Clinic, Medan Marelan District. The statistical test used the Chi Square test with a statistical significance p value of 0.05. After conducting research on statistical data tests, it was found that the increase in body weight during pregnancy has a relationship with the incidence of preeclampsia in pregnancy. There is a significant relationship between weight gain during pregnancy and the incidence of preeclampsia in pregnancy, with a p value of 0.003